2017
DOI: 10.1111/trf.14192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of starting material (fresh versus cryopreserved marrow) on mesenchymal stem cell culture

Abstract: This study demonstrates that MSCs derived from cryopreserved marrow have the same growth characteristics as fresh marrow-derived MSCs. Further studies are needed to explore potential differences in clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…As with the study by Kaplan et al, cryopreservation did not significantly affect cell proliferation, but trends demonstrated higher rates in FC MSCs on day 10 ( p = 0.07, Fig. 2b) [33]. Similarly, the clonogenic capacity was also higher in fresh MSCs as compared to FT MSCs ( p < 0.05, Fig.…”
Section: Discussionsupporting
confidence: 76%
“…As with the study by Kaplan et al, cryopreservation did not significantly affect cell proliferation, but trends demonstrated higher rates in FC MSCs on day 10 ( p = 0.07, Fig. 2b) [33]. Similarly, the clonogenic capacity was also higher in fresh MSCs as compared to FT MSCs ( p < 0.05, Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have documented success in recovering viable nucleated cells from cryopreserved bone marrow [15,16,23,24]. However, the primary focus of these earlier studies was on the culture expansion of progenitor cells for clinical use and not the quantification of the initial progenitor cell content.…”
Section: Discussionmentioning
confidence: 99%
“…Strong correlations have been observed between pre-freeze and postthaw bone marrow across several cell populations, including mononuclear cells, committed myeloid precursors and hematopoietic stem cells [14]. Additionally, connective tissue progenitor cells have been recovered from cryopreserved bone marrow and successfully culture expanded with clinical applications in mind [15,16]. Although several groups have performed the CFU-F assay with both fresh and cryopreserved bone marrow and reported no differences between the two, data are limited [15] or not shown [17].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the administration of MSCs with a high viability is required to target an improvement in efficacy. Recent experimental data on the comparison of different cell products reports that fresh BM-MSCs are 14% more viable compared to cryopreserved ones [172]. Furthermore, delivery of MSC immediately upon thawing instead of thawing and washing the MSCs could enhance MSC viability, as observed by Matthay MA et al [71].…”
Section: Clinical Trials-demonstrating Safety In Ardsmentioning
confidence: 91%